Indonesian initiatives on building regional health regime in Southeast Asia after Covid-19 - Ludiro Madu; Aryanta Nugraha (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article discusses Indonesia's endeavours in developing a Southeast Asian health regime, with an emphasis on its role as the head of foreign policy and global health in 2020, despite the obstacles posed by the COVID-19 pandemic. As ASEAN member nations cope with budget limits, differences in healthcare services, and the need to balance national and regional interests, the epidemic has highlighted the significance of a robust and coordinated regional health regime. Indonesia has been a key player in promoting health diplomacy and encouraging regional cooperation, calling for a coordinated and cohesive response to the epidemic and future health catastrophes. The article also examines ASEAN member nations' attempts to improve regional health monitoring, share efficient procedures, and promote fair access to healthcare. It points out the significance of strong political commitment, partnership, and sustainable approaches in establishing a more solid and cohesive regional health regime.